Honouring Inuit Women’s Educational and Employment Experiences through Indigenous Storywork Methodology - Wasilik, Tina (Alberta Academic Review, 2021)
The legacy of the Arctic Residential School system is still present in Nunavut education today. Inuit in Nunavut continue to receive a westernized education that does not fully encompass traditional Inuit learning principles. However, a group of Inuit women, enrolled in a Northern College Early Childhood Education (ECE) Diploma Program from 2015-2017, uniquely blended a child-centred educational approach with traditional Inuit learning methods.Through the Inuit women’s practicum placements completed at a preschool, they developed self-confidence and a skill set that led to their employment and self-reliance. The Oxford dictionary defines self-reliance as “the ability to do or decide things by yourself, rather than depending on other people for help” (Oxford University Press 2021). This definition does not fully capture the essence of self-reliance from Inuit women’s perspectives. Their self-reliance is greatly tied to a combination of domestic work, wage work, and land-related work that forms a unique framework to capture the specificity of northern women’s self-reliance. My research study will explore the personal experiences of these Inuit women graduates. The study intends to inform institutional decision-making, determine how to best support the Inuit women’s educational access and success, contribute to the scholarly work in the field of education and advance future Inuit training and employment initiatives. My research questions are: What does self-reliance look like from an Inuit woman’s point of view? How did participating in the 2015-2017 ECE Diploma Program influence the Inuit women’s lives? Indigenous Storywork is grounded in Indigenous Research Framework (Lavallée 2009) which allows for connections between people, their ancestors, and the natural world. Indigenous Storywork guides my study theoretically and methodologically. I will use Storywork to engage in holistic meaning-making that involves the heart (emotions), mind (intellect), body (physical actions), and spirit (spirituality) (Archibald et ...